Pemberdayaan Masyarakat Melalui Pemnafaatan Dana PEM dan Pekarangan Untuk Budidaya Hortikultura dan Obat-Obatan Disertai Pendidikan Kewirausahaan Bagi Orang Dewasa - Liem, Jhon Sepron D.; Roni M. Ndun; Vidensia Bergita Anin; Naisanu, Joritha; Henny A. Raga; Darmanto F. Kisse; Deby M. Malelak (Universitas Mataram, 2025)
This community service activity aimed to empower residents of Manulai II Sub-district, Kupang City, East Nusa Tenggara, through the utilization of Community Economic Empowerment Funds (PEM) and home yard land for the cultivation of horticultural and medicinal plants, combined with entrepreneurship education for adults. The main problems addressed were the low utilization of yard land and PEM funds for productive purposes, as well as the lack of entrepreneurial knowledge among the community. The implementation methods included community education through counseling sessions, technical training, cultivation demonstrations, and entrepreneurship mentoring. A total of 25 adult participants took part in a series of training and hands-on practices. Evaluation results through pre-test and post-test instruments showed significant improvement in participants’ knowledge and skills in both cultivation and entrepreneurship aspects. Additionally, participants demonstrated initiative in developing small-scale home-based businesses. The conclusion of this activity is that an integrative approach involving PEM fund utilization, yard optimization, and entrepreneurship education has proven effective in enhancing the local community’s economic capacity. This model has the potential to be replicated in other areas with similar social conditions and local resources